Health Care Workers Knowledge About Privatization Of Medical Services And Revenue Development At Saudi Arabia 2024 (The Review of Diabetic Studies, 2024)
BackgroundVision 2030 represents Saudi Arabia’s strategic Privatization of Medical Services and Revenue Development at Saudi Arabia. Launched in April 2016, this vision describes an innovative healthcare plan to improve services and outcomes. Privatization of Medical Services and Revenue Development at Saudi Arabia. This assessment summarises Vision 2030s healthcare revolution. This study explores the Privatization of Medical Services and Revenue Development at Saudi Arabia Saudi healthcare. Prior to Vision 2030, Saudi Arabia’s healthcare system grappled with escalating costs and a heavy reliance on foreign labour, signalling a need for transformative change. Vision 2030s patient-centric framework emphasises individualised treatment, and the National Guidelines Centre's .In addition, we also explored the new initiative of Electronic Health Records and telemedicine services. Additionally, we addressed the challenges associated with it, such as the imperative to address the digital divide and ensure data security. Vision 2030 in Saudi Arabia brought about a significant transformation in the provision of healthcare. Despite the presence of challenges, such as inadequate infrastructure, insufficient personnel, and resistance to change, this vision offers a robust foundation for effectively tackling these concerns. Aim of the study: To assessment health care workers knowledge about Privatization of Medical Services and Revenue Development at Saudi Arabia 2024. Method: This is a cross-sectional study targeting health care workers in Saudi Arabia. Two validated questionnaires were used, the first validated questionnaire focuses on assessment the knowledge about Privatization of Medical Services and Revenue development.Results: shows that the majority of participants age 40-49 years  were (35.0%)  and 30-39 years of age were (19.0%), while < 30 years and above 50 were respectively (20.0,26.0%), regarding gender the majority of participant  male were (61.0%) but female were (39.0%),Conclusion: Saudi Arabia’s healthcare is advancing thanks to Vision 2030, proving recent efforts were fruitful . Vision 2030s healthcare model provides a comprehensive foundation for meaningful progress in a variety of healthcare settings. Even though some don’t want change, the Model of Care is growing in popularity since everyone wants to meet Vision 2030s healthcare goals. Saudi healthcare experts are adapting to the country’s fast-growing population. Their efforts centre on this.